2010
DOI: 10.5194/acp-10-7617-2010
|View full text |Cite
|
Sign up to set email alerts
|

High variability of the heterogeneous ice nucleation potential of oxalic acid dihydrate and sodium oxalate

Abstract: Abstract. The heterogeneous ice nucleation potential of airborne oxalic acid dihydrate and sodium oxalate particles in the deposition and condensation mode has been investigated by controlled expansion cooling cycles in the AIDA aerosol and cloud chamber of the Karlsruhe Institute of Technology at temperatures between 244 and 228 K. Previous laboratory studies have highlighted the particular role of oxalic acid dihydrate as the only species amongst a variety of other investigated dicarboxylic acids to be capab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 62 publications
5
43
0
Order By: Relevance
“…In case of lower heterogeneous ice nucleability, the aerosol particles will again be activated to a droplet cloud at point A2. Our previous experiments have shown that potentially immersed oxalic acid dihydrate crystals might then not get instantly and completely dissolved on the typical timescale of an expansion cooling experiment (Wagner et al, 2010). The embedded crystals therefore still can act as condensation mode ice nuclei in this experiment and could provoke the glaciation of the droplet cloud before the homogeneous freezing temperature of pure water droplets has been reached at point A3.…”
Section: Experimental Trajectories Of Aida Expansion Cooling Experimentsmentioning
confidence: 99%
See 3 more Smart Citations
“…In case of lower heterogeneous ice nucleability, the aerosol particles will again be activated to a droplet cloud at point A2. Our previous experiments have shown that potentially immersed oxalic acid dihydrate crystals might then not get instantly and completely dissolved on the typical timescale of an expansion cooling experiment (Wagner et al, 2010). The embedded crystals therefore still can act as condensation mode ice nuclei in this experiment and could provoke the glaciation of the droplet cloud before the homogeneous freezing temperature of pure water droplets has been reached at point A3.…”
Section: Experimental Trajectories Of Aida Expansion Cooling Experimentsmentioning
confidence: 99%
“…We have recently observed a similar discrepancy for the efflorescence behaviour of oxalic acid. Whereas several previous studies have reported on the difficulty to effloresce oxalic acid particles even at very low relative humidities of less than 5% (Braban et al, 2003;Mikhailov et al, 2009;Prenni et al, 2001), supercooled aqueous oxalic acid solution droplets readily crystallised in AIDA at 244 K and 70% RH on a time scale of about one hour (Wagner et al, 2010). As outlined in our recent work, we will attempt to quantitatively analyse the crystallisation process in future chamber studies by exploiting the potential of a novel light scattering instrument (Small Ice Detector probe SID3, University of Hertfordshire) to determine the crystallisation rate.…”
Section: Ice Nucleation Studies In the Ternary Nacl/oa/h 2 O Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…A detailed description of the chamber preparation, the chamber instrumentation, and the expansion cooling technique for ice cloud studies is given in the recent papers by Wagner et al (2010Wagner et al ( , 2011. In the following, we therefore only give a brief introduction to the chamber and its intrumentation.…”
Section: The Cloud Simulation Chamber Aidamentioning
confidence: 99%